Dynamics of strong radio sources with UMRT-II / Mohammed Awid Al-Amri - Al-Amri, Mohammed Awid (2010)
Radio astronomy is a new field in Southeast Asia. University Malaya Radio Telescope UMRT-II is located on the roof of Block B in the Department of Physics, University of Malaya to detect neutral hydrogen emission line. Doppler shift of 1420.4 MHz for different radio sources were observed to determine their dynamics. By measuring the Doppler shift, the velocity V, of each radio source can be determined. Hence the dynamic of radio source can be deduced. The radio spectrum of Coma Cluster was also analyzed and its dark matter content was estimated. The observation time effort was investigated for Coma Cluster spectra detection and it was found that the dark matter mass significantly high. It was successfully concluded that longer observation time improves spectrum detection of weak radio sources. The observations of neutral hydrogen emission line were interfaced by man-made radio frequencies from unknown sources. This type of radio frequency is called Radio Frequency Interference (RFI). Two surveys for RFI at two sites were done. The first one was at the same site of our radio telescope UMRT-II, at the Department of Physics, University Malaya, and the second one was at another site (Lubuk China, Malacca). For these surveys, a simple technique was used using a discone antenna, Low Noise Amplifier (LNA) and a 2 GHz spectrum analyzer.